2012
DOI: 10.1167/iovs.11-9162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of SD-OCT Features and Retinal Sensitivity in Neovascular Age-Related Macular Degeneration

Abstract: PURPOSE. To correlate retinal sensitivity in patients with neovascular age-related macular degeneration (AMD) with specific characteristics of retinal morphology.METHODS. Thirty eyes of 30 patients presenting with active choroidal neovascularization were examined by spectral domain optical coherence tomography (SD-OCT) and microperimetry (MP-1). Image-processing software was used to match a fundus photographic (FP) MP-1 image with an infraredþOCT SD-OCT image. Each MP test point for retinal sensitivity was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
1
42
2
Order By: Relevance
“…This can be explained by the significant improvement of VA and improvement in stability of fixation, as well as the learning curve of patients. As opposed to Sulzbacher et al [7] who reported a strong negative correlation between central retinal thickness and central retinal sensitivity (r = -0.509, p= 0.004), we found no statistically significant correlation between the percentage of change in point thickness and the percentage of change in point sensitivity except for the lower nasal quadrant (r =-0.426, p= 0.019). This can be partially explained by the fact that the increase in retinal sensitivity in our study was not as marked as the decrease in retinal thickness or the increase in BCVA, which were both significantly high.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This can be explained by the significant improvement of VA and improvement in stability of fixation, as well as the learning curve of patients. As opposed to Sulzbacher et al [7] who reported a strong negative correlation between central retinal thickness and central retinal sensitivity (r = -0.509, p= 0.004), we found no statistically significant correlation between the percentage of change in point thickness and the percentage of change in point sensitivity except for the lower nasal quadrant (r =-0.426, p= 0.019). This can be partially explained by the fact that the increase in retinal sensitivity in our study was not as marked as the decrease in retinal thickness or the increase in BCVA, which were both significantly high.…”
Section: Discussioncontrasting
confidence: 99%
“…Central foveal thickness (CFT) was measured in microns, inner segment/outer segment (IS/OS) junction integrity and Retinal Pigment Epithelium (RPE) band were assessed. The IS/OS was graded as complete if the hyper reflective line (Interface) between the IS/OS was present, as discontinuous if the line was interrupted and the segments were only partly visible, or as completely absent [7]. The RPE layer was graded as complete if the hyper reflective band was continuous, as discontinuous if the RPE was disrupted and only partly visible, or as absent if no band was visible [7].…”
Section: Patients' Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Its uses are both clinical and for research. 7,8,9,10,11 In the present study we assess CQ and HCQ toxicity using microperimetry. Our purpose is to describe the value of microperimetry as a high sensitivity test for the screening of CQ and HCQ retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…8 In an extended step, the functional treatment response of distinct initial SD-OCT findings was evaluated using the followup mode of both imaging devices.…”
mentioning
confidence: 99%